FACTORS INFLUENCING THE LATE DELIVERY OF PROJECTS IN STATE-OWNED ENTERPRISES: THE CASE OF ESKOM - Flepisi, Lubabalo; Mlambo, Courage (The South African Journal of Industrial Engineering, 2021)
Delays in project completion by state-owned enterprises are a major concern and a threat to the South African economy. This study investigates both the internal and the external factors influencing the late delivery of projects in state-owned enterprises, with ESKOM as a case study. The research design was a survey questionnaire that was used to gather sufficient information. The study revealed key internal and external factors influencing the late delivery of projects in the state-owned enterprises, including the failure to update construction programmes, the late delivery of contractor-supplied materials, corruption, and political interference. In conclusion, we posit that, to ensure early project completion, the authorisation and empowerment of the project team is vitally important.